(untitled) (New York, 2007)
21st Century Astronomy’s distinctive writing style, superior art, and supporting media package all work together to teach students how science works, help students visualize basic concepts and physical processes, and keep students focused on the “big picture.”
Keywords: Astronomy,Thiên văn học